FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SECARA ONLINE PADA KELOMPOK REMAJA - Rizky (2020)
This study uses quantitative descriptive methods conducted at Shopee e-commerce. Shopee, one of the e-commerce companies, is a mobile market in the Shopee application, which was first launched in December 2015. The purpose of this research is to study and prove whether purchases at Shopee e-commerce are in accordance with promotions, prices, and trust. The population in this study is a group of teenagers who have shopped online at Shopee. Samples taken were 75 respondents by random sampling method. By distributing questionnaires to groups of teenagers who have shopped online at Shopee during the data collection process. The data analysis technique used is descriptive analysis and inferential analysis with the analytical tool used is PLS (Partial Least Square). The results showed that the variable price promotion and trust determine and significant to the purchase decision.